Informal Science and Youth Development: Creating Convergence in Out-of-School Time. Issue 13 (April 2014) - Noam, Gil G.; Shah, Ashima Mathur
This chapter highlights the fit between youth-development-oriented programming and informal science activities in out-of-school time (OST) and illustrates how science and youth development can and should co-occur. The clover model and Dimensions of Success tool are introduced as lenses for designing and assessing science program quality in OST. "While both the afterschool and science fields are at a crossroads, association with the other enhances the potential for each to flourish." ∼Lucy Friedman (2005)